Analisis Yuridis terhadap Tindak Pidana Kekerasan Seksual terhadap Penyandang Disabilitas (Studi Putusan Nomor 1245/Pid.B/2023/PN Mdn) - Anastasia Anjali Tanjung; Iin Hot Prinauli Purba (CV WAHANA PUBLIKASI, 2026)
Sexual violence against persons with disabilities constitutes a serious violation of human rights because victims are particularly vulnerable and often face barriers in accessing justice and legal protection. This study aims to analyze the legal regulation of sexual violence against persons with disabilities in Indonesian legislation and to examine the implementation of Decision Number 1245/Pid.B/2023/PN Mdn in providing legal protection for victims with disabilities. This research employs normative legal research using statutory and case approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively through legal interpretation. The findings indicate that legal protection is regulated under the Indonesian Criminal Code, Law Number 8 of 2016 concerning Persons with Disabilities, Law Number 12 of 2022 concerning Sexual Violence Crimes, and Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. However, the Criminal Code remains general in nature and does not specifically address the protection of persons with disabilities. In contrast, the subsequent laws provide more comprehensive protection through accessibility, legal assistance, victim protection, rehabilitation, restitution, and recovery. In Decision Number 1245/Pid.B/2023/PN Mdn, the court recognized the victim's intellectual disability as an aggravating circumstance and convicted the offender under Law Number 12 of 2022. Nevertheless, the judgment did not explicitly provide restitution or comprehensive rehabilitation for the victim. The study concludes that Indonesia's legal framework has become more progressive, but its implementation still requires stronger victim-oriented and restorative protection.